Multiplicative Methods of Action in the Modern Ossetia Language: A Repeatable Return Method of Action (Compared with the Russian Language) (Proceedings of Southern Federal University. Philology, 2019)
Alina A. Levitskaya (Stavropol, Russian Federation)The study of the similarities and differences between Russian and Ossetian multi-action verbs of various modes of action due to different combinations of universal and idio-ethnic components of aspectually relevant semantics suggests that the expression of the multiplicative mode of action in the Ossetian language differs markedly from the designation of multiplicativeness in modern Russian and reflects the specificity of “vision” of situations in this linguistic picture of the world with an obvious universality of meanings associated with objective plurality character of action.Key words: multiplicativeness, way of a verb action, semantic type of repeatedness, modern Ossetia language.DOI 10.23683/1995-0640-2019-3-21-33